2021
DOI: 10.1093/ntr/ntab066
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Adjunct to Nicotine Patch Facilitates Smoking Cessation and May Reduce Post-Cessation Weight Gain: A Pilot Randomized Controlled Trial

Abstract: Introduction Approved pharmacological treatments for smoking cessation are modestly effective, underscoring the need for improved pharmacotherapies. Glucagon-like peptide-1 receptor (GLP-1R) agonists attenuate the rewarding effects of nicotine in preclinical studies. We examined the efficacy of extended-release exenatide, a GLP-1R agonist, combined with nicotine replacement therapy (NRT, patch) for smoking cessation, craving and withdrawal symptoms, with post-cessation body weight as secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…According to ClinicalTrials.gov, three human clinical trials are investigating the potential effects of a GLP‐1 receptor agonist against tobacco use disorder (Table 2), and one randomized clinical pilot trial has investigated the effects of exenatide, 2.0 mg once weekly, in combination with transdermal nicotine replacement therapy on smoking cessation. They have reported that exenatide increased smoking abstinence and reduced craving (Yammine et al, 2021). Two other clinical trials investigating subcutaneous liraglutide, 3.0 mg daily (ClinicalTrials.gov identifier NCT03712098), and subcutaneous dulaglutide, 1.5 mg once weekly (ClinicalTrials.gov identifier NCT03204396), are still recruiting.…”
Section: Role Of Glp‐1 In Substance Use Disordermentioning
confidence: 99%
“…According to ClinicalTrials.gov, three human clinical trials are investigating the potential effects of a GLP‐1 receptor agonist against tobacco use disorder (Table 2), and one randomized clinical pilot trial has investigated the effects of exenatide, 2.0 mg once weekly, in combination with transdermal nicotine replacement therapy on smoking cessation. They have reported that exenatide increased smoking abstinence and reduced craving (Yammine et al, 2021). Two other clinical trials investigating subcutaneous liraglutide, 3.0 mg daily (ClinicalTrials.gov identifier NCT03712098), and subcutaneous dulaglutide, 1.5 mg once weekly (ClinicalTrials.gov identifier NCT03204396), are still recruiting.…”
Section: Role Of Glp‐1 In Substance Use Disordermentioning
confidence: 99%
“…In a pilot study, extended-release exenatide, a GLP-1R agonist, added to the nicotine patch, improved abstinence, reduced craving and withdrawal symptoms and decreased PSCWG among abstainers. Findings suggested that the GLP-1R agonist strategy is worthy of further research in larger studies with longer durations [ 165 ].…”
Section: Medications For Smoking Cessation and Weight Gainmentioning
confidence: 99%
“…Importantly, exenatide crosses the blood brain barrier (20), and a similar dosing regiment, i.e. 2 mg subcutaneously once weekly, has recently shown efficacy in other neuropsychiatric disorders including nicotine dependence (21) and Parkinson's disease (20) suggesting a central engagement, possibly mediated, at least in part, by dopamine signaling (22).…”
Section: Introductionmentioning
confidence: 99%
“…Since the pharmacodynamics and pharmacokinetics of a GLP-1 receptor agonist in patients with AUD have not been investigated, we chose a dosing regimen consistent with established tolerability and efficacy in treatment of type 2 diabetes, i.e., exenatide, 2 mg subcutaneously once weekly. Importantly, exenatide crosses the blood-brain barrier ( 20 ), and a similar dosing regimen, i.e., 2 mg subcutaneously once weekly, has recently shown efficacy in other neuropsychiatric disorders, including nicotine dependence ( 21 ) and Parkinson’s disease ( 20 ), suggesting a central engagement, possibly mediated, at least in part, by dopamine signaling ( 22 ).…”
Section: Introductionmentioning
confidence: 99%